2012
DOI: 10.7857/jsge.2012.17.3.039
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effect of a Weir Construction on the Groundwater Flow System

Abstract: Visual MODFLOW, a three dimensional groundwater flow model, was used to analyze effects of a weir construction in an alluvial stream on the nearby groundwater flow system. A hypothetical conceptual model was developed to investigate how the groundwater level and the water budget could change after a weir construction depending on the location of tributary streams. A site example, dealing with the Juksan weir installed in the Yeongsan River, was also demonstrated to predict the effects of the weir construction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Similarly, the groundwater flow from the main stream to the channel also occurred within the old river channel. Jeong and Koo (2012) predicted similar results to our observations that the direction of groundwater flow in the Yeongsan River would be changed by the construction of the Juksan weir. Installation of new drainage channels was suggested as a countermeasure to drawdown the groundwater level.…”
Section: Changes In Stream-aquifer Interactionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the groundwater flow from the main stream to the channel also occurred within the old river channel. Jeong and Koo (2012) predicted similar results to our observations that the direction of groundwater flow in the Yeongsan River would be changed by the construction of the Juksan weir. Installation of new drainage channels was suggested as a countermeasure to drawdown the groundwater level.…”
Section: Changes In Stream-aquifer Interactionsupporting
confidence: 90%
“…This also affects groundwater discharge, thus a flood control effect is expected. Results of a groundwater flow model predicted the change of direction in groundwater flow in the Juksan area (Jeong and Koo ). This would lead to streams changing from gaining to losing streams, leading to changes in the groundwater quality and the water balance between the Yeongsan River and the local aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows the groundwater level response rate following a change in the river level due to the opening of the four weirs. The response rate (R) was calculated as follows: R = r GW r SW (1) where r GW and r SW are calculated slopes of observed decline of water level change with time in groundwater and river water, respectively. The response rate increased with increasing transmissivity, which means that the transmissivity of the aquifer is an important factor for determining the response rate.…”
Section: Analysis Of Groundwater Level Declinementioning
confidence: 99%
“…As part of the Four Major Rivers Restoration Project, 16 weirs were constructed on four major rivers in South Korea from 2010 to 2012, which helped to meet water demands during the dry season and control flooding. Many studies have shown that hydraulic structures such as weirs and dams are useful for replenishing groundwater resources [1,2]. Water filling at the weir caused an increase in the groundwater level during the dry season [3], while river level management at the Changnyong-Hamman weir in the Nakdong River resulted in a decline in the average groundwater level during the wet season [4].…”
Section: Introductionmentioning
confidence: 99%